Glass transitions in the cellular Potts model. (1st December 2016) - Chiang, M.; Marenduzzo, D.
Abstract: We study the dynamical transition between a fluid-like and a solid-like phase in a confluent cell monolayer, by using the cellular Potts model and computer simulations. We map out the phase diagram as a function of interfacial tension and of cell motility. While in the fluid phase there is normal diffusion, in the solid phase we observe sub-diffusion, very slow relaxation, and ageing, thereby strongly suggesting that this phase is glassy. Our results complement previous theoretical work within the vertex model and show that the cellular Potts model can account for the experimentally observed glassy dynamics of some biological tissues.